Simple, inexpensive, and ergonomic phantom for quality assurance control of MRI guided Focused Ultrasound systems - Antoniou, Anastasia; Damianou, Christakis A. (My University, 2023)
The popularity of Magnetic Resonance guided Focused Ultrasound (MRgFUS) as a beneficial therapeutic solution for many diseases is increasing rapidly, thus raising the need for reliable quality assurance (QA) phantoms for routine testing of MRgFUS systems. In this study, we propose a thin acrylic film as the cheapest and most easily accessible phantom for assessing the functionality of MRgFUS hardware and software.
Keywords: Acrylic film; Cheap; MRI; Phantom; Quality assurance; Ultrasound